2021
DOI: 10.1186/s12935-021-01868-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of m6A methyltransferase component VIRMA in multiple human cancers (Review)

Abstract: N6-Methyladenosine (m6A) modification is one of the most widely distributed RNA modifications in eukaryotes. It participates in various RNA functions and plays vital roles in tissue development, stem cell formation and differentiation, heat shock response control, and circadian clock controlling, particularly during tumor development. The reversible regulation of m6A modification is affected by the so-called ‘reader’, ‘writer’ and ‘eraser’. As a required component and the largest methyltransferase, vir-like m6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 77 publications
(197 reference statements)
0
35
0
Order By: Relevance
“…VIRMA has an oncogenic role in other tumor models [56][57][58][59][60], including urological malignancies [29]. Indeed, our previous observations highlighted frequent VIRMA upregulation in primary TGCTs (which was also confirmed in an independent study analyzing multiple cancer types [22]), with strong VIRMA immunoexpression found in 72.4% of samples and, in particular, in 84.2% of metastatic patient samples [3,10]. For those reasons, we aimed at a better understanding of the biological implications in TGCTs.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…VIRMA has an oncogenic role in other tumor models [56][57][58][59][60], including urological malignancies [29]. Indeed, our previous observations highlighted frequent VIRMA upregulation in primary TGCTs (which was also confirmed in an independent study analyzing multiple cancer types [22]), with strong VIRMA immunoexpression found in 72.4% of samples and, in particular, in 84.2% of metastatic patient samples [3,10]. For those reasons, we aimed at a better understanding of the biological implications in TGCTs.…”
Section: Discussionmentioning
confidence: 80%
“…In a previous work, we have proven the relevance of VIRMA (also known as KIAA1429) in these tumors [10]. VIRMA (or vir-like m 6 A methyltransferase associated) is a critical part of the methyltransferase complex (which includes METTL3, the catalytic component, as well as other players such as WTAP and METTL14 that work together to stabilize and allow the functionality of the complex) and was shown to contribute to cancer progression in multiple malignancies by regulating cell cycle progression, migration, invasion, resistance to apoptosis and tumor growth, in both m 6 A dependent and independent manners [22]. In our cohort of 122 TGCT patients, VIRMA (and the m 6 A reader YTHDF3) was found to be significantly upregulated (at both transcript and protein levels) in SE compared to NS subtypes, confirming in silico data reporting these two m 6 A-related players as the most upregulated in TGCTs.…”
mentioning
confidence: 99%
“…In endometrial cancer, it was reported to be downregulated and to modulate the expression of members of the AKT pathway and inhibit cell proliferation ( Cai et al, 2018 ; Visvanathan et al, 2018 ; Miao et al, 2019 ; Peng et al, 2019 ; Li et al, 2020 ; Liang et al, 2020 ; Nombela et al, 2021 ). KIAA1429 was reviewed to be upregulated in 12 types of cancers and to be downregulated in 4 cancer types ( Zhu et al, 2021 ). METTL16 was found to be overexpressed in colorectal cancer and to be underexpressed in hepatocellular carcinoma, affecting activation of multiple metabolic pathways ( Liu et al, 2019 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these regulators, vir-like m6A methyltransferase associated (VIRMA), a “writer” of m6A regulators, promotes the progression of cancer and is associated with shorter survival for patients with multiple types of cancer, such as kidney renal clear cell carcinoma, kidney renal papillary cell carcinoma, and papillary thyroid carcinoma ( Zhu et al, 2021 ). However, no reports have examined the correlation between VIRMA expression and OC progression.…”
Section: Discussionmentioning
confidence: 99%